Magnetic resonance and applanation tonometry for noninvasive determination of left ventricular load and ventricular vascular coupling in the time and frequency domain. Issue 6 (June 2016) - Adji, Audrey; Kachenoura, Nadjia; Bollache, Emilie; Avolio, Alberto P.; O'Rourke, Michael F.; Mousseaux, Elie
Abstract : Objectives: Cardiac magnetic resonance (CMR) is potentially more useful than Doppler ultrasound for quantifying ascending aortic flow velocity in the presence of complex flow patterns. Our aim was to characterize flow velocity wave patterns in the ascending aorta with age and their use with central (carotid) pressure waves to estimate ascending aortic impedance as left ventricular (LV) load and interpret vascular/ventricular interaction. Methods: Ascending aortic flow velocity was measured noninvasively, using velocity-encoded CMR, in 50 healthy individuals (21–70 years) by averaging flow velocities across the aortic cross-section. Pressure waves were measured noninvasively by carotid tonometry as a surrogate of aortic pressure. Impedance was determined in modulus and phase from corresponding harmonics of pressure and flow velocity waves. Results: With increasing age, ascending aortic peak flow velocity decreased from 67 ± 18 cm/s in younger persons (≤50 years) to 48 ± 13 cm/s in older persons (>50 years) ( P  < 0.0001), largely attributable to increase in aortic diameter 2.5 ± 0.3 cm for third decade to 3.3 ± 0.2 cm for seventh decade ( P  < 0.001). With ageing, carotid pressure augmentation index increased ( r 2  = 0.52, P  < 0.001), as expected from increased aortic stiffness, whereas ascending aortic flow pressure augmentation index decreased during the mid-to-late systolic period ( r 2  = 0.26, P  < 0.001), attributable to progressive impairment in LV contractility. Ascending aortic impedance spectra showed ageing changes seen in previous invasive studies and as predicted from modelling. Conclusion: CMR provides noninvasive measures of LV pulsatile load in time and frequency domain, with expected differences between young and older persons. This conforms with and extends the new American Heart Association recommendations for LV afterload and vascular/ventricular interaction.